Tapping Diversity From the Wild: From Sampling to Implementation - Hübner, Sariel; Kantar, Michael B. (Frontiers in Plant Science, 2021)
The diversity observed among crop wild relatives and their ability to flourish in unfavorable and harsh environments have drawn the attention of plant scientists and breeders for many decades. However, it is also recognized that the benefit gained from using crop wild relatives in breeding is a potential rose between thorns of detrimental genetic variation that is linked to the trait of interest. Despite the increased interest in crop wild relatives, little attention was given so far to the statistical, analytical, and technical considerations that should guide the sampling design, the germplasm characterization, and later its implementation in breeding. Here, we review the entire process of sampling and identifying beneficial genetic variation in crop wild relatives and the challenge of using it in breeding. The ability to detect beneficial genetic variation in crop wild relatives is strongly affected by the sampling design which should be adjusted to the spatial and temporal variation of the target species, the trait of interest, and the analytical approach used. Moreover, linkage disequilibrium is a key factor that constrains the resolution of searching for beneficial alleles along the genome, and later, the ability to deplete linked deleterious genetic variation as a consequence of genetic drag. We also discuss how technological advances in genomics, phenomics, biotechnology, and data science can improve the ability to identify beneficial genetic variation in crop wild relatives and to exploit it in strive for higher-yielding and sustainable crops.